Fabrication of Antibacterial and Antioxidant ZnO-Impregnated Amine-Functionalized Chitosan Bio-Nanocomposite Membrane for Advanced Biomedical Applications - Ali M. Ali; Abdelrahman M. Hamed; Mahmoud A. Taher; Mohamed H. Abdallah; Mohamed Abdel-Motaleb; Zyta M. Ziora; Ahmed M. Omer (Molecules, 2023)
Developing a variety of safe and effective functioning wound dressings is a never-ending objective. Due to their exceptional antibacterial activity, biocompatibility, biodegradability, and healing-promoting properties, functionalized chitosan nanocomposites have attracted considerable attention in wound dressing applications. Herein, a novel bio-nanocomposite membrane with a variety of bio-characteristics was created through the incorporation of zinc oxide nanoparticles (ZnONPs) into amine-functionalized chitosan membrane (Am-CS). The developed ZnO@Am-CS bio-nanocomposite membrane was characterized by various analysis tools. Compared to pristine Am-CS, the developed ZnO@Am-CS membrane revealed higher water uptake and adequate mechanical properties. Moreover, increasing the ZnONP content from 0.025 to 0.1% had a positive impact on antibacterial activity against Gram-positive and Gram-negative bacteria. A maximum inhibition of 89.4% was recorded against Escherichia coli, with a maximum inhibition zone of 38 ± 0.17 mm, and was achieved by the ZnO (0.1%)@Am-CS membrane compared to 72.5% and 28 ± 0.23 mm achieved by the native Am-CS membrane. Furthermore, the bio-nanocomposite membrane demonstrated acceptable antioxidant activity, with a maximum radical scavenging value of 46%. In addition, the bio-nanocomposite membrane showed better biocompatibility and reliable biodegradability, while the cytotoxicity assessment emphasized its safety towards normal cells, with the cell viability reaching 95.7%, suggesting its potential use for advanced wound dressing applications.